2019
DOI: 10.1002/cam4.2320
|View full text |Cite
|
Sign up to set email alerts
|

CBX2 is a functional target of miRNA let‐7a and acts as a tumor promoter in osteosarcoma

Abstract: Osteosarcoma is the most common type of primary malignant tumor of skeletal with poor prognosis in children and adolescents. Accumulating evidence indicates that CBX2 is overexpressed in multiple human neoplasm and play a critical role in tumorigenesis and progression. However, its functional role and upstream regulation mechanism in osteosarcoma remain unknown. In the present study, tissue microarray (TMA) analysis was performed to determine the association between CBX2 expression and clinical prognosis of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…CBX2, a member of chromobox family, is an essential regulator of cancer progression and the cell cycle ( 28 ). It has been reported that CBX2 exerts an oncogenic effect on osteosarcoma progression and promotes osteosarcoma cell proliferation and metastasis ( 29 ). A previous study demonstrated that CBX2 knockdown markedly suppressed the proliferation of hepatocellular carcinoma cells and promoted apoptosis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…CBX2, a member of chromobox family, is an essential regulator of cancer progression and the cell cycle ( 28 ). It has been reported that CBX2 exerts an oncogenic effect on osteosarcoma progression and promotes osteosarcoma cell proliferation and metastasis ( 29 ). A previous study demonstrated that CBX2 knockdown markedly suppressed the proliferation of hepatocellular carcinoma cells and promoted apoptosis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromobox homolog 2 (CBX2), one of the member proteins in CBX family, is a necessary regulator of gene expression [40]. Increasing evidence indicates that abnormal expression of CBX2 plays important roles in various cancers, such as prostate cancer, osteosarcoma, and breast cancer [41, 42]. Interestingly, we discovered that CBX2 served as the downstream target gene of miR-497-5p, constituting the CASC9/miR-497-5p/CBX2 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that the expression of CBX2 is closely related to tumorigenesis and tumor development. Some studies have shown that the expression of CBX2 in osteosarcoma tissue is signi cantly increased, and the degree of the increase is closely related to metastasis, postoperative recurrence, chemotherapy reaction and adverse prognosis [16]. In advanced serous ovarian cancer, the expression of CBX2 was signi cantly increased.…”
Section: Discussionmentioning
confidence: 99%